Effect of different Additives on Bale Silage Quality of Maize Fodder - Khanday, Zahid Bashir (Indian Journal of Animal Nutrition, 2021)
The present study was conducted to evaluate the effect of different additives on the bale silage quality of maize fodder. An experiment was conducted with four different treatments of maize fodder before bailing them. These treatments consisted of; without additive (MF0), Lactobacillus casei @ 106 CFU/g (NCDC-17) of fresh fodder (MFLAB), Silotan, a commercial product @15ml/100 Kg of fresh maize fodder (MFST) and Formaldehyde @0.5% of fresh maize fodder (MFFA) as silage additives. The bale silage of four such treatments MF0, MFLAB, MFST and MFFA, in replications (3*9 treatments) was prepared by using a high power 100 kg bailing machine. Each treatment was evaluated after 60 days of ensiling in terms of quality parameters, chemical composition, fermentation characteristics, microbial (LAB) counts and In vitro DM degradability. The evaluation of bale silage revealed a significant increase (p